Penanganan Pembiayaan Muarabahah yang Bermasalah di Kopersi Jasa Keuangan Syariah Mandiri Sejahtera Cabang Campurejo Panceng Gresik - Agus Setiawan; Miftahul Amin; Nashihin (Al-Muzdahir : Jurnal Ekonomi Syariah, 2019)
KJKS- Mandiri Sejahtera Campurejo Branch is a sharia-based cooperative engaged in financial services in Panceng District, Gresik Regency. One of them is murabaha financing. This cooperative in distributing murabahah financing has internal and external obstacles, including: factors from the management of KJKS- Mandiri Sejahtera Campurejo Branch itself as well as factors from customers. Based on the above background, the authors conducted a study entitled Handling Problems with Murabahah Financing at the Mandiri Sejahtera Syariah Financial Services Cooperative, Campurejo Panceng Gresik Branch. The research that the writer did was included in the descriptive qualitative research. And in collecting data, the author uses the method of observation, interviews or interviews and documentation. As for the analysis, the author uses the SMART analysis technique. The handling of problematic murabahah financing at KJKS- Mandiri Sejahtera Campurejo Branch has used procedures in accordance with existing theories, namely: Given invoices, rescheduling, confiscation of guarantees and execution of guarantees. The factors causing the occurrence of problematic murabahah financing at KJKS-Mandiri Sejahtera Campurejo Branch are: Internal factors caused by officers and the system. While external factors are caused by customers or conditions. Handling problematic murabahah financing at KJKS- Mandiri Sejahtera Campurejo Branch, although there are procedures that are in accordance with theory, the manager prefers to pray and discuss the reasons for: 1. According to the manager praying is the first step so that God opens the door of the customer's heart, 2. Discussions aimed at influencing beliefs that can change their behavior and also do not pose the risk of physical or mental clashes